PERGESERAN PERAN PEMERINTAH TERHADAP PENGAWASAN ORGANISASI KEMASYARAKATAN BERDASARKAN UNDANG-UNDANG ORGANISASI KEMASYARAKATAN DI INDONESIA - Islami, Muhammad Izzul; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Based on the number of Community Organizations that were born since the tap was opened by the government, the government took steps or roles by issuing Legislation regarding Community Organizations, the quick step taken was to issue Government Regulations in lieu of Laws (Perppu), namely Perppu Number 2 Year 2017 regarding amendments to Law Number 17 of 2013 concerning Social Organizations issued and signed by President Jokowi on July 10, 2017 and approved by the House of Representatives as Law through Plenary Session on October 24, 2017. This research is a normative legal research, because it is based on library research which takes excerpts from reading books, literature, or supporting books that have relation to the problem to be studied, assisted with primary, secondary and tertiary data sources. This study uses qualitative data analysis and produces descriptive data. From the results of the study, it was concluded that, First, in the current CSO Law namely Law Number 16 Year 2017 there was a reduction in the portion of the government's role in CSO oversight compared to the previous CSO Law. Which, Law No.17 of 2013 has increased the role of government in supervision compared to Law No. 8 of 1985. In the future, a better arrangement in the future is to increase the number of regulations that focus on government oversight of CSOs, such as how to model development and empowerment of CSOs. So that with a more massive supervision and set forth in the organization of Mass Organizations, it will provide the right to freedom of association to be more accommodated and directed in accordance with our country's ideology, Pancasila. The author's suggestion is, First, it must re-adjust the role of the government, especially in monitoring CSOs by revising Law 16 of 2017 on this CSO or making special regulations for the supervision of CSOs so that they are in accordance with Pancasila and / or the 1945 Constitution and maintain the spirit of freedom of opinion and gather around. Secondly, In addition to increasing regulations that focus on oversight of CSOs, it can also add instruments by involving the Constitutional Court in the supervision of CSOs, especially in interpreting ideologies that are contrary to the 1945 Constitution. Because the state institution that has the right to interpret the Constitution is the Constitutional Court. Keywords: Oversight, CSOs, Role of Government